Konsep Amar Ma’ruf Nahi Munkar Dalam Tafsir Al-Munir Karya Wahbah Al-Zuhaili: - Idlofi Idlofi; Ahmad Rezy Meidina (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This article attempts to examine the concept of amar ma'ruf nahi munkar initiated by Wahbah al-Zuhaili in his commentary book al-Munir. The behavior of amar ma'ruf nahi munkar which has been misunderstood because there is no standard concept offered by the Qur'an has become an interesting discourse. The development of the times has contributed to influencing the concept of amar ma'ruf nahi munkar, in which each era has its own moral values and ideas adapted to the context of its society. This article is intended to provide understanding to the public regarding amar ma'ruf nahi munkar. The conclusion in this paper uses a normative approach, with the aim of trying to reveal the values of truth in society so that it should be actualized in the future. As for the findings that Wahbah al-Zuhaili said: that before doing amar ma'ruf nahi munkar one must have knowledge, both religious sciences and social sciences. Keywords: Wahbah Al-Zuhaili, Tafsir Al-Munir, Amar Ma'ruf, Nahi Munkar